Is rs242561 a regulator of tau expression in adult mice?. (20th December 2022) - DAS, Rueben G; Choi, Eirene; Sgourdou, Paraskevi; Bernard, Tia; Dombroski, Beth A.; Schellenberg, Gerard D.
Abstract: Background: Microtubule associated protein tau ( MAPT ) is a major risk gene for multiple neurodegenerative diseases including Progressive supranuclear palsy (PSP), Corticobasal degeneration (CBD) and Alzheimer's disease (AD) where disease specific imbalance in 3R: 4R tau isoforms is noted. Since pathogenic mutations in the coding region of MAPT is minimal in these diseases, it is likely that the deviation from the normal equimolar concentration of 3R: 4R tau is due to altered regulation through its regulatory elements. One such potential regulator is suspected to be MAPT intronic SNP, rs242561. This SNP lies within NRF2‐bound anti‐oxidant response element and is actively transcribed in hippocampus but repressed in most non‐brain tissues. It is also a chromHMM enhancer in substantia nigra. However, expression studies on this SNP are discordant and inconclusive. In the present study we investigate whether rs242561 has any role in tau regulation in mice. Method: We deleted 756 bp sequence encompassing the syntenic base of rs242561 in mouse by CRISPR‐Cas9 genome editing. Brain tissues from cortex, cerebellum and hippocampus were dissected from adult wild type, heterozygous and homozygogus mice with the deletion to study expression of tau. Result: We observed reduced level of tau in cortical tissues of adult heterozygous and homozygous mice (heterozygote< homozygote) than the wild type but not in hippocampus and cortex. Conclusion: Our preliminary study suggests rs242561 might have a role in regulating the expression of tau in adult mice cortex.